Stiglitz Versus the IMF on the Asian Debt Crisis: An Intertemporal Model with Real Exchange Rate Overshooting. - Kirsanova, T; Menzies, G; Vines, D (CEPR, 2007)
This paper develops a real model of financial crisis, and uses it to elucidate the controversy between Joe Stiglitz and the IMF concerning the Asian financial crisis. Borrowers of foreign capital are bound by lending contracts to pay the world rate of return on their borrowing, following an adverse shock; by assumption, they do not default. This is onerous, since the shock makes the marginal product of capital fall to less than the world rate of return, and creates a debt overhang on which interest must be paid. The country faces a choice. It could choose to pay these extra interest obligations on its debt overhang--a transfer--in every period, raise taxes in order to meet these obligations, and thereby gradually reduce capital to its new lower level, at which point there would no longer be a debt overhang. We describe this as the 'IMF strategy'. Alternatively the country could choose the 'Stiglitz strategy': it could immediately borrow internationally the sum of all the future interest obligations on its debt overhang, perhaps with the assistance of the IMF. It would need to raise taxes in order to meet the interest costs on that extra borrowing. But the fiscal cost of doing this would be finite and the fiscal costs would be equally spread across time. The short run tax burden would thus be smaller. We show that balance sheet effects mean that the real exchange rate can greatly overshoot in the IMF strategy, whereas it need not overshoot in the Stiglitz strategy. That will lessen the 'crisis' aspects of the short run responses to the shock.